The Influence of Consumer Behavior and Marketing Mix Based on Digital Marketing on Purchasing Decisions (Case Study of Shabby Pink Store Consumers in Medan City) - Sarah Melinda Sihombing; Nur Aisyah (MultiTech Publisher, 2023)
This study aims to determine